Rate after-effects fail to transfer cross-modally: evidence for distributed sensory timing mechanisms - Motola, Aysha; Heron, James; McGraw, Paul V.; Roach, Neil W.; Whitaker, David (Nature Publishing Group, 2018)
Accurate time perception is critical for a number of human behaviours, such as understanding speech and the appreciation of music. However, it remains unresolved whether sensory time perception is mediated by a central timing component regulating all senses, or by a set of distributed mechanisms, each dedicated to a single sensory modality and operating in a largely independent manner. To address this issue, we conducted a range of unimodal and cross-modal rate adaptation experiments, in order to establish the degree of specificity of classical after- effects of sensory adaptation. Adapting to a fast rate of sensory stimulation typically makes a moderate rate appear slower (repulsive after-effect), and vice versa. A central timing hypothesis predicts general transfer of adaptation effects across modalities, whilst distributed mechanisms predict a high degree of sensory selectivity. Rate perception was quantified by a method of temporal reproduction across all combinations of visual, auditory and tactile senses. Robust repulsive after-effects were observed in all unimodal rate conditions, but were not observed for any cross-modal pairings. Our results show that sensory timing abilities are adaptable but, crucially, that this change is modality-specific - an outcome that is consistent with a distributed sensory timing hypothesis.